PENGARUH BENTUK DAN UKURAN GERAM SEBAGAI BAHAN BAKU TERHADAP KEKERASAN PRODUK EKSTRUSI PANAS - Angga Febrianto; Rusnaldy Rusnaldy (JURNAL TEKNIK MESIN, 2015)
Machining process will always produce the chips. In general, Chips produced with indirect process will be removed, but sold and melted down again to get new material. Research and development division was expected to reduce the cost of manufactures products from raw materials by simple process and low energy so that, it can reduce the price of the product and customers will consider it. The research and engineering efforts required to design metal forming process that is expected to produce new materials with good quality use method compaction, sintering, and hot extrusion is proposed. Recycling aluminium chips from three several parameters turning were obtained with Feed rate 0.09 rev/min, Cutting speed 140 Rpm, (specimens one); Feed rate 0.459 rev/min, Cutting speed 320 Rpm, (specimens two); Feed rate 0.459 rev/min, Cutting speed 850 Rpm, (specimens three). This chips were cut until size of material is 40 mesh, then compacted by 20 ton force, sintering with temperature 440oC and terminated by hot extrusion. In order to determine the quality of products, there are several tests that must be used such as micro hardness test. The best micro hardness is 57.30 HV (top), 66.30 HV (under), 71.82 HV (edge), 58.40 HV (top inside), 58.70 HV (under inside). From these results show the higher feed rate and cutting speed will make micro hardness will be better.